Respon Pertumbuhan dan Hasil Terung Ungu (Solanum melongena L.) pada Konsentrasi dan Interval Waktu Pemberian Air Kelapa - Anandamurti, I Wayan Krisnayogi; Wijana, Gede; Astawa, I Nyoman Gede (Agrotrop : Journal on Agriculture Science; Vol 14 No 1 (2024), 2024)
Growth Response and Yield of Purple Eggplant ( Solanum melongena L.) on Concentration and Time Interval Giving Coconut Water. The production of purple eggplant ( Solanum melongena L.) which is still quite low can be overcome by the use of growth regulators in plant cultivation activities. This study aims to determine the effect of giving coconut water concentration and time intervals to increase the growth and yield of purple eggplant. This study used a factorial Randomized Block Design with 2 factors; first factor: concentration of coconut water 0%, 15%, 25%, and 35%; second factor: time interval of giving coconut water once every 4, 5, 6, and 7 days; with 3 repetitions. The observed variables are; Plant height (cm), Number of leaves (pc), Leaf area (mm2), Leaf chlorophyll, At the time of flower emergence (dap), Number of fruit per plant (pc), Fruit weight per plant (g), Fruit length (cm), Diameter of fruit (mm), Weight of fruit per fruit (g), Oven dry weight of fruit (g), Fresh weight of stover (g), Dry weight of stover (g). The results showed that the concentration and interval of administration of coconut water had a very significant interaction on flowering age and significantly on fruit diameter and fruit weight per fruit in the combination treatment which consisted of 15% coconut water and was given once every 5 days; giving coconut water has a very significant effect on plant height (71.17 cm), number of leaves (25.33 strands), and fruit oven dry weight (1.09 g), where the best treatment is by giving 15% coconut water; the timing of administration of coconut water had a very significant effect on fresh weight of stover (335.92 g) once every 6 days and had a significant effect on fruit oven dry weight (8.50 g) once every 4 days.